Marketing for business growth - Levitt, Theodore (McGraw-Hill, 1974)
The book talks about three generalk topics: how to think about and get more from the products, people, and resources; how to think sensibly about and get innovation and imitation in marketing; and how to think about marketing's claim on company resources relative to other considerations which must go into charting the purposes and managing the various functions of the whole organization.